2023
DOI: 10.1096/fj.202201580r
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide CRISPR screen identifies the CCT chaperonin as a critical regulator of vesicle trafficking

Abstract: Vesicle trafficking is a fundamental cellular process that controls the transport of various proteins and cargos between cellular compartments in eukaryotes. Using a combination of genome‐wide CRISPR screening in mammalian cells and RNAi screening in Caenorhabditis elegans, we identify chaperonin containing TCP‐1 subunit 4 (CCT4) as a critical regulator of protein secretion and vesicle trafficking. In C. elegans, deficiency of cct‐4 as well as other CCT subunits impairs the trafficking of endocytic markers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…We detected multiple components of the TRiC molecular chaperone complex (CCT8, TCP1, CCT6A, CCT3 and CCT4), that was also enriched as GO term (Supplementary Fig. 10d; Supplementary Data 8) and, in fact, CCT4 was recently implicated as a crucial vesicular trafficking regulator 56 . We validated CCT8, as well as TP53BP2, as NEDD4 Ub substrates by WB (Fig.…”
Section: Bioe3 Identifies Nedd4 Substratesmentioning
confidence: 99%
“…We detected multiple components of the TRiC molecular chaperone complex (CCT8, TCP1, CCT6A, CCT3 and CCT4), that was also enriched as GO term (Supplementary Fig. 10d; Supplementary Data 8) and, in fact, CCT4 was recently implicated as a crucial vesicular trafficking regulator 56 . We validated CCT8, as well as TP53BP2, as NEDD4 Ub substrates by WB (Fig.…”
Section: Bioe3 Identifies Nedd4 Substratesmentioning
confidence: 99%
“…They consist of a spherical proteolipid bilayer membrane, and contain specific proteins, RNA molecules and DNA molecules 144 . Recent studies have demonstrated that CCT4 is a key regulator of vesicle trafficking, 145 and the levels of CCT subunits were found to be upregulated in various cancer exosomes 146,147 . Additionally, the levels of six of the eight CCT subunits (CCT1, CCT2, CCT3, CCT5, CCT6A and CCT7) were found to be significantly increased in glioblastoma cell‐derived extracellular vesicles, and CCT6A in glioblastoma tissue showed a potential link with EGFR and was identified as a potential prognostic biomarker 146 .…”
Section: Cct Subunits In Cancersmentioning
confidence: 99%